Binge eating disorder: a symptom-level investigation of genetic and environmental influences on liability - Mitchell, K. S. (2010)
BACKGROUND: Recent behavioral genetic studies have emphasized the importance of investigating eating disorders at the level of individual symptoms, rather than as overall diagnoses. We examined the heritability of binge eating disorder (BED) using an item-factor analytic approach, which estimates contributions of additive genetic (A), common environmental (C), and unique environmental (E) influences on liability to BED as well as individual symptoms. METHOD: Participants were 614 monozygotic and 410 dizygotic same-sex female twins from the Mid-Atlantic Twin Registry who completed a self-report measure of BED symptoms based upon DSM-IV criteria. Genetic and environmental contributions to BED liability were assessed at the diagnostic and symptom levels, using an item-factor approach. RESULTS: Liability to BED was moderately heritable; 45% of the variance was due to A, with smaller proportions due to C (13%), and E (42%). Additive genetic effects accounted for 29–43% of the variance in individual items, while only 8–14% was due to C. CONCLUSIONS: Results highlight the relevance of examining eating disorders at the symptom level, rather than focusing on aggregate diagnoses.